The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5851/kosfa.2019.e51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aged and Fermented Garlic Extracts as Natural Antioxidants on Lipid Oxidation in Pork Patties

Abstract: The aim of this study was to investigate the natural antioxidant activity of raw garlic (RG), aged black garlic (AG), and garlic fermented with Bacillus subtilis (FG) extracts on pork patty lipid oxidation throughout refrigerated storage. The total polyphenol, total flavonoid content, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activity of three different types of garlic extracts were measured. The total phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
5
5
0
1
Order By: Relevance
“…The copyright holder for this preprint this version posted August 13, 2021. ; https://doi.org/10.1101/2021.08.13.456289 doi: bioRxiv preprint with 10% aqueous ginger extract had lower TVB-N value of 14.23±0.62 compared to 84.00±0.40 and 18.86±0.12 and 22.87±0.47 for pork mixed with 10% aqueous onion and ginger extracts respectively. The TVB-N value obtained in this study of 22.87±0.47 for pork mixed with 10% aqueous garlic extract was lower compared to 25, 22.5 and 15 mg/100 g meat for pork patties mixed 0.5% freeze-dried, freeze-dried fermented and freeze-dried aged garlic extract in a similar study conducted in Korea [54].…”
Section: Total Volatile Basic Nitrogen (Tvb-n) Content Of Frozen Chevon and Porksupporting
confidence: 55%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted August 13, 2021. ; https://doi.org/10.1101/2021.08.13.456289 doi: bioRxiv preprint with 10% aqueous ginger extract had lower TVB-N value of 14.23±0.62 compared to 84.00±0.40 and 18.86±0.12 and 22.87±0.47 for pork mixed with 10% aqueous onion and ginger extracts respectively. The TVB-N value obtained in this study of 22.87±0.47 for pork mixed with 10% aqueous garlic extract was lower compared to 25, 22.5 and 15 mg/100 g meat for pork patties mixed 0.5% freeze-dried, freeze-dried fermented and freeze-dried aged garlic extract in a similar study conducted in Korea [54].…”
Section: Total Volatile Basic Nitrogen (Tvb-n) Content Of Frozen Chevon and Porksupporting
confidence: 55%
“…At 14 d of frozen storage, pork mixed with 10% aqueous ginger extract had lower TVB-N value of 14.23±0.62 compared to 84.00±0.40 and 18.86±0.12 and 22.87±0.47 for pork mixed with 10% aqueous onion and ginger extracts respectively. The TVB-N value obtained in this study of 22.87±0.47 for pork mixed with 10% aqueous garlic extract was lower compared to 25, 22.5 and 15 mg/100 g meat for pork patties mixed 0.5% freeze-dried, freeze-dried fermented and freeze-dried aged garlic extract in a similar study conducted in Korea[54].The increase in TVB-N values during storage of animal muscles is related to protein and amino acid breakdown by proteolytic gram-negative bacteria and enzymes[55]. It is reported that the presence of microbes like lactic acid bacteria, Brochothrix thermosphacta, Enterobacteriaceae and…”
supporting
confidence: 51%
“…Several studies have been conducted to measure the efficacy of BG extract in meat products, in which the extensive protection of quality of spent duck nugget during storage was observed ( Lishianawati et al, 2021 ). In addition, the inhibition of lipid oxidation in pork patties was also observed following treatment with aged and fermented garlic extracts ( Lee et al, 2019 ). However, to the best of our knowledge, sufficient information on its inclusion effect on RTE chicken soup products is not well presented, particularly with that of pre-treated BG extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides their nutritional value and therapeutic properties for food systems, the addition of natural antioxidants may present a safer strategy against lipid oxidation. Several studies have reported the antioxidant capacity and use of garlic and leek as natural antioxidants (Khan, Soumen, Malik, & Shakeel, 2017; Kovarovič et al., 2019; Lee, Yoon, Lee, & Lee, 2019; Mariutti, Nogueira, & Bragagnolo, 2011). However, the effect of leek and the combination of leek and garlic against cholesterol oxidation have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%